Genomic and Epigenetic Complexity of the FOXF1 Locus in 16q24.1: Implications for Development and Disease - V. Dharmadhikari, Avinash; Szafranski, Przemyslaw; V. Kalinichenko, Vladimir; Stankiewicz, Pawel (Current Genomics, 2015)
The FOXF1 (Forkhead box F1) gene, located on chromosome 16q24.1 encodes a member of the FOX family of transcription factors characterized by a distinct forkhead DNA binding domain. FOXF1 plays an important role in epithelium-mesenchyme signaling, as a downstream target of Sonic hedgehog pathway. Heterozygous point mutations and genomic deletions involving FOXF1 have been reported in newborns with a lethal lung developmental disorder, Alveolar Capillary Dysplasia with Misalignment of Pulmonary Veins (ACDMPV). In addition, genomic deletions upstream to FOXF1 identified in ACDMPV patients have revealed that FOXF1 expression is tightly regulated by distal tissue-specific enhancers. Interestingly, FOXF1 has been found to be incompletely paternally imprinted in human lungs; characterized genomic deletions arose de novo exclusively on maternal chromosome 16, with most of them being Alu-Alu mediated. Regulation of FOXF1 expression likely utilizes a combination of chromosomal looping, differential methylation of an upstream CpG island overlapping GLI transcription factor binding sites, and the function of lung-specific long non-coding RNAs (lncRNAs). Foxf1 knock-out mouse models demonstrated its critical role in mesoderm differentiation and in the development of pulmonary vasculature. Additionally, epigenetic inactivation of FOXF1 has been reported in breast and colorectal cancers, whereas overexpression of FOXF1 has been associated with a number of other human cancers, e.g. medulloblastoma and rhabdomyosarcoma. Constitutional duplications of FOXF1 have recently been reported in congenital intestinal malformations. Thus, understanding the genomic and epigenetic complexity at the FOXF1 locus will improve diagnosis, prognosis, and treatment of ACDMPV and other human disorders associated with FOXF1 alterations.
Keywords: Gene regulation